Cladistic analysis of reproductive, behavioral, sociobiological, and developmental traits in the Hominoidea - Duda, Pavel (Jihočeská univerzita, 2008)
The available information concerning reproduction, ontogeny, behavioral patterns and social relationships in all species of extant and some extinct were analysed cladistically. The character set was optimized on the phylogeny of the Hominoidea, and the particular common ancestors were reconstructed. The study reveals that all common ancestors (excluding the common ancestor of Pan spp.) showed more or less gorilla-like patterns of behavior and social system. The major outcome of this study is the finding that humans, despite universal assumptions, are (in terms of behavior and sociobiology) rather slightly derived gorillas than substantially derived chimpanzees.
Cladistic analysis of reproductive, behavioral, sociobiological, and developmental traits in the Hominoidea
Keywords: Hominoidea; phylogeny; behavior; human evolution; sex